Aprendizagem e engajamento como função de consequências para o desempenho de crianças em um programa de ensino individualizado de leitura - Veiga, Dhayana Inthamoussu (2014)
The individualized teaching program for elemental reading and writing skills Learning to Read and Write in Small Steps has been systematically developed and improved for the last 25 years. Anecdotal observations suggested a reduction on the engagement of children in the program, indicating need to study motivational‟ variables in this context. The purpose of the present study was to analyze learning and task engagement of children during the application of Module 1 of the Program: 1) in its standard version (Standard-Procedure) and 2) in a token version, where points were added to a counter in correct trials exchanged for video access as supplementary consequences (Token- Procedure). Two experiments were conducted in an elementary public school with 21 children without or with incipient reading repertoire. In the Experiment 1, participants were nine boys and four girls with 8-10 years of age of the 3rd and 4th grade. Some participants were exposed to Standard-Procedure and others to Token-Procedure. Learning measures provided by the program and systematic observational measures (ten seconds partial interval recording) assessed performance. On-Task and Off-Task behaviors (participants‟) and Task Assistance and On-Task Request behaviors (experimenter‟s) were recorded in five sessions per participant. Results showed that all participants had meaningful gains in reading, spelling and equivalence performance, with teaching and recombination words, and the advancement in the procedure occurred within a number of sessions similarly to programmed teaching steps. An overall reduction trend of average latency to perform task along units was observed. The average latency in Token-Procedure was significantly lower than in Standard- Procedure. More promptness to perform task was interpreted as evidence of its greater evocative effectiveness, probably due its correlation with a more effective consequence. It suggests that the effects of standard consequences were supplemented by the introduction of points. All participants systematically engaged in the task during the teaching sessions and Off-Task behaviors occurred more variably and apparently without interfering in task performance, except in some cases. Off-task behaviors appeared to be mostly an artifact of the discrete-trial procedure, in which the task cannot occur continuously. The results of Experiment 1 led to Experiment 2, in which the parameters of point accumulation and of its exchange were adjusted (Token‟- Procedure). Participants were six boys and two girls, with 6-9 years, of 2nd or 3rd grade, with lower initial repertoire and were only partially exposed to Token‟- Procedure. Their performance differ significantly in relation to other participants, such as a higher number of repetitions of teaching steps and less gains of target repertoires, which impaired the observation of possible effects of Token‟-Procedure. Despite of the limitations of this study, its results indicate important directions for future studies on the determinants of task engagement of children in this Program.